Vitamin C and cancer – a review - Godlewski, Dariusz; Wojtyś, Piotr; Bury, Przemysław (Contemporary Oncology/Współczesna Onkologia, 1999)
This article reviews published epidemiologic research on the association of vitamin C with cancer risk. Extremely strong and consistent inverse relationship exists between vitamin C intake and risk for cancer arrising from esophagus, stomach, colon, rectum, breast and cervics. Vitamin C prevents oxidative damage and inhibits the reaction of nitrosation.